Fortifying network attached storage: Implementation of multifactor authentication and drive sharing protocol for robust data protection for DLSU CCS TSG - Samsico, Aaron Earl DG. (Animo Repository, 2023)
Strong data security and secure access control have become essential with the increasing reliance on Network Attached Storage (NAS) systems. The NAS infrastructure being used by De La Salle University College of Computer Studies which is being managed by Technical Support Group is the subject of this capstone project's security enhancements. The project aims to achieve this through the implementation of multifactor authentication and a drive sharing protocol. The major goal of this project is to improve existing security measures by introducing multifactor authentication, which adds an additional layer of protection by requiring another form of authentication which in this case is via an authenticator application. By adopting multifactor authentication, unauthorized access to the NAS system will be considerably reduced, guaranteeing that only authorized users can view and modify the stored data. Alongside this, a drive sharing protocol will be developed to facilitate secure and controlled file sharing within the DLSU CCS TSG, allowing administrators to define and enforce access permissions, and allowing specific users or groups to access and collaborate on shared drives while maintaining strict data integrity and confidentiality. The successful completion of this project will dramatically improve the security posture of the DLSU CCS TSG's NAS infrastructure, protecting important data from unwanted access, data breaches, and potential data loss. Furthermore, the project will serve as a great model for other organizations looking to increase their NAS security, emphasizing the need of multifactor authentication and secure drive sharing protocols in protecting data confidentiality and integrity in network storage systems. Keywords: Multifactor Authentication, Drive Sharing Protocol, Network Attached Storage, Access Matrix, 2-Factor Authentication